INTRAOPERATIVE ULTRASOUND IN LOCALIZING NONPALPABLE BREAST LESIONS - Zečić, Katarina; Zečić, Ognjen (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Intraoperative ultrasound in breast tumor surgery is a relatively new technique used for localizing nonpalpable breast lesions. This procedure has multiple advantages over wire needle localization (WNL), which is a standard approach to localizing nonpalpable breast lesions. It has been shown that intraoperative application of ultrasound is presented with a decrease in tumor-infiltrated resection margins, and with less excised healthy tissue around the tumor.Aim: The purpose of this article is to evaluate the success rate of nonpalpable breast lesion excisions by localizing them with intraoperative ultrasound.Material and methods: This is a retrospective study, which involves patients from the Department of surgical oncology at “Bežanijska kosa” from January 2013 to December 2017. Medical records of the patients who were not operated for nonpalpable breast lesions using intraoperative ultrasound were isolated. Success rate of identifying and excising nonpalpable lesions is presented in percentages, so this finding can be compared to other published studies. Results: Of the 2627 patients operated on during this period, 317 (11.9%) patients had nonpalpable lesions, of which 173 were localized by WNL, and 144 were localized by intraoperative ultrasound (IOUS). Of 144 patients whose lesions were localized by IOUS, 61 patients had breast cancer, while 83 patients had benign lesions. Based on the medical records, all non-palpable lesions were successfully located and excised with intraoperative ultrasound (144/144- 100%).Conclusion: Intraoperative ultrasound represents an optimal technique for localizing nonpalpable breast lesions that are visible on ultrasound and are an indication for surgical removal.
Keywords: intraoperative ultrasound; breast; nonpalpable lesion